2021
DOI: 10.3389/fimmu.2021.680055
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Affects the Immunosuppressive Function of Group 2 Innate Lymphoid Cells in Human Non-Small Cell Lung Cancer

Abstract: BackgroundThere is increasing evidence that group 2 innate lymphoid cells (ILC2s) play an essential role in allergy and parasitic infection. However, the role of ILC2s in human lung cancer remains unclear.MethodsILC2s from peripheral blood mononuclear cells (PBMCs) obtained from healthy donors (HDs) and non-small cell lung cancer (NSCLC) patients, and NSCLC tumor tissues were analyzed via multicolor flow cytometry. ILC2s or CD14+ cells were sorted by fluorescence-activated cell sorting. qPCR and flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
(61 reference statements)
6
21
0
Order By: Relevance
“…In addition, blood and tumor-infiltrating human ILC1 were shown to express PD-1/ PDCD1 [ 111 ]. These include non-small cell lung, breast and gastrointestinal tumor-infiltrating ILC1 [ 124 , 163 ].…”
Section: Ilc Expression Of Ic—parallel With Adaptive Immune Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, blood and tumor-infiltrating human ILC1 were shown to express PD-1/ PDCD1 [ 111 ]. These include non-small cell lung, breast and gastrointestinal tumor-infiltrating ILC1 [ 124 , 163 ].…”
Section: Ilc Expression Of Ic—parallel With Adaptive Immune Cellsmentioning
confidence: 99%
“…We, and others, have shown that IL-33 and γc cytokines also induce PD-1 expression [ 44 , 46 , 170 , 179 , 180 ]. PD-1 is mainly expressed by KLRG1 + ILC2 [ 170 ] and negatively regulates ILC2 proliferation and cytokine expression [ 44 , 46 , 124 , 163 , 170 , 178 , 179 , 181 , 214 ] ( Figure 2 ). PD-1-deficient mice ( Pdcd1 −/− ) have increased peripheral ILC2 [ 46 , 170 ], with enhanced KLRG1 expression and cytokine production [ 170 ] compared with wildtype animals.…”
Section: Ilc Expression Of Ic—parallel With Adaptive Immune Cellsmentioning
confidence: 99%
See 3 more Smart Citations